Exterior view of the Mandapa of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Pictured here is a view of the south elevation of the mandapa (pillared hall) of the Suhaveshwar Temple. The mandapa has two lateral transepts on the north and south sides. The exterior of the transepts has plinth mouldings that support a plain wall which is ornamented with pilaster motifs. The dwarf walls have slender and slanting kakshasana (seat backs) that have balustrade designs. Both the vedika (wall) and the slanting seat back of the kakshasana are bereft of ornamentation patterns.